Job satisfaction and leadership behavior brief measures: A development and validation study (2023)
Job satisfaction and leadership behavior are recognized by the organizational world as fundamental elements that influence the overall effectiveness of a company. However, as the first step for an adequate intervention on any of these variables, it is the evaluation. The purpose of this paper is to develop and validate two brief measures on job satisfaction and leadership behavior.